Community/public health nursing practice : health for families and populations - Maurer, Frances A.; Smith, Claudia M. (St. Louis, Missouri : Elsevier, cop., 2013)
Offers a practical approach that helps you to learn and apply core concepts of community and public health nursing. This title provides numerous real-life examples that demonstrate your roles and responsibilities as a community health nurse.
Responsibilities for care in community / public health nursing -- Origins and future of community / public health nursing -- The United States health care system -- Financing of health care: context for community / public health nursing -- Global health -- Legal context for community / public health nursing practice -- Epidemiology: unraveling the mysteries of disease and health -- Communicable diseases -- Environmental health risks: at home, at work, and in the community -- Relevance of culture and values for community / public health nursing -- Home visit: opening the doors for family health -- A family perspective in community / public health nursing -- Family case management -- Multiproblem families -- Community assessment -- Community diagnosis, planning, and intervention -- Evaluation of nursing care with communities -- Health promotion and risk reduction in the community -- Screening and referral -- Health teaching -- Vulnerable populations -- Disaster management: caring for communities in an emergency -- Violence: a social and family problem -- Adolescent sexual activity and teenage pregnancy -- Substance use disorders -- Rehabilitation clients in the community -- Children in the community -- Older adults in the community -- State and local health departments -- School health -- Home health care -- Rural health -- Community mental health.
Includes bibliographical references and index.
Keywords: COMMUNITY HEALTH NURSING